Three-dimensional printing of polymeric scaffolds with micro/nano-scale topographies for cartilage and bone tissue engineering. - Prasopthum, Aruna (2020)
Cells in their natural 3D environment experience a variety of topographies of the extracellular matrix (ECM) from micro- to nanoscales, which play a pivotal role in permitting normal cellular/tissue functions. Micro-/nanoscale topographies of materials alone were found to modulate various stem cell behaviours such as changes in cell adhesion morphologies and actin cytoskeletal organisation, which collectively directed intracellular signalling pathways towards stem cell growth and differentiation. However, the explored systems used in the previous studies on cell-material interactions are 2D, which did not necessarily represent in vivo cell/tissue microenvironments. The ability of precisely and reproducibly controlling architectures has made 3D printing a beneficial technology for making tissue-engineered scaffolds. However, the impacts of surface topographies of 3D printed scaffolds on stem cell behaviours have been under-explored whilst insight into the topography-mediated stem cell differentiation in 3D is crucial for designing a smart implantable scaffold. Herein, a novel, facile and low-cost 3D printing approach (so-called ‘micro-extrusion printing’) for two printing ink formulations, allowing direct incorporation of defined ECM-mimicking micro-/nanotopographies onto the 3D printed strut surfaces, was developed. This direct approach removed the need for 3D printing of a sacrificial mould and subsequent mould removal compared to the previous indirect 3D printing. The first printing ink formulation relied upon thermally-induced phase separation of a poly(L-lactide)/tetrahydrofuran solution to create a printable physical gel whilst the second ink formulation utilised an agitation method to introduce bubbles into a viscously printable polycaprolactone/dichloromethane gel. Self-supporting 3D printed scaffolds with ECM-mimicking nanofibrous and micro-/nanoporous strut surfaces were created from the first and the second polymer gels, respectively. Agitation was found to be a prerequisite for the formation of strut micro-/nanopores, which is the mechanism that has not previously been reported. The nanofibrous strut surface enhanced fibronectin absorption, adhesion and chondrogenic differentiation of mesenchymal stem cells (MSCs) whilst the strut pores were found to promote chondrogenesis and osteogenesis of MSCs in the absence of soluble differentiation factors and affect cell morphology and differentiation differently in the presence of differentiation factors. The 3D printing approach developed herein could potentially be used for a wide range of biomedical applications where the desirable personalised architectures and the ECM-mimicking topographies are required.